The impact of automated control of indoor air pollutants on cardiopulmonary health, environmental comfort, sleep quality in a simulated apartment: A crossover experiment protocol - Pantelic, Jovan; Aristizabal, Sara; Liu, Qingyang; Senerat, Araliya; Son, Young Joo; Byun, Kunjoon; Li, Linhao; Mullan, Aidan; Zhang, Rongpeng; Johnson, Bruce D.; Clements, Nicholas (Frontiers in Built Environment, 2023)
Air pollution makes an impact on cardio-pulmonary health. Since people spend over 90% of their time indoors, exposures to the indoor environment make the most significant impact on health. Among indoor sources, cooking emits the most particles that disperse through the residential indoor environment and expose occupants. We use fully controlled simulated residential modules to conduct exposure experiments. In the pilot study, participants stayed in modules for 1 week, and in the main study, 14 participants will stay in the module for 4 weeks. One module is operated as a classical US house air supply recommendation. The second module has an advanced control system that, alongside the standard air supply, activates air quality interventions: stove hood, portable air cleaners, bathroom exhaust and air flush (increasing air supply ~3 times) as a function of the PM2.5 levels in the space. Environmental sensors based on Internet of Things technology simultaneously monitored PM2.5 CO2, TVOC, RH and air temperature in all spaces and operated air quality interventions. Participants scheduled activities include morning and evening tasks, Monday through Friday. Participants may leave the module during the day. They will be asked to cook breakfast and dinner using lab-provided recipes. We measured each participant’s blood pressure, heart rate, and heart rate variability. Blood and urine samples were collected 3 times per participant in the pilot and will be collected 2 times a week in the main study. Up to 20mL of blood and a minimum of 30mL of urine will be sampled per collection. Analysis of blood and urine was performed for 8-hydroxy-2-deoxyguanosine (8-OHdG, urine), von Willebrand Factor (vWF, blood plasma), high sensitivity C-Reactive Protein (hsCRP, blood serum), Interleukin-6 (blood plasma), CD11b (blood), Fibrinogen (blood plasma), and Myeloperoxidase (blood serum). We conducted a Pilot for 2 weeks with 3 participants to test the study protocol and data collection. We adjusted the protocol for the main study based on the pilot results. Results showed that the proposed study protocol could be completed, and the methodology adopted in this study will provide valuable insights into the relationship between exposure to cooking particles and occupants' health.